Conservation value of grassy road verges in plantation-dominated forest steppe - Botond Magyar; Róbert Gallé; Péter Batáry; Attila Torma (Global Ecology and Conservation, 2025)
Forest plantations, often consisting of non-native tree species, are widespread globally, including the Great Hungarian Plain at the western edge of the Eurasian Forest Steppe zone. Protecting the isolated remnant habitats alone is insufficient to maintain the biodiversity within production landscapes. Linear landscape elements (LLE), such as road verges, can serve as corridors and refuges for species, though their benefits may be limited. To assess the conservation value of dirt road verges between pine plantations, we compared their orthopteran communities with those of natural forest-steppe fragments and extensive pastures as reference habitats. We hypothesized similar conservation value across habitats but expected differences in species composition. We found no significant differences in species richness, abundance, functional diversity, or Grasshopper Conservation Indices between habitats, indicating comparable conservation value. However, species composition was more similar between forest-steppe and road verges than between pastures and road verges. Road verges also supported more small-bodied, low-dispersal orthopterans than pastures. We concluded that dirt road verges between pine plantations sustain high-quality habitat and landscape functional connectivity, conserving various grasshopper species, including sensitive and range-restricted species. We suggest that the verges of unpaved, low-traffic, and irregularly managed dirt roads should receive more attention in efforts to enhance the green infrastructure of fragmented landscapes. These road verges, especially those between plantations, may also play a role in forest-steppe restoration and should be considered in related planning efforts.